PENCIPTAAN MOTIF BATIK UNTUK SERAGAM(UNIFORM) CIVITAS AKADEMIKA ISI SURAKARTA SEBAGAI UPAYA PENCITRAAN INSTITUSI YANG BERKARAKTER - Marwati, Sri (Institut Seni Indoensia Surakarta, 2010)
Batik is one of the Indonesianâ€™s prides. The government, batik craftsman, and people have tried many efforts to preserve batik. We have to be proud of for based on the decision of the United Nations Educational, Scientific, and Cultural Organization (UNESCO) it is decided that batik Indonesia is considered to be an intangible cultural Heritage of Humanity. Batik as a uniform of a community or an institution is actually able, psychologically, to bring it to the sense of kinship, togetherness, and solidarity. Batik as a uniform is also able to form peopleâ€™s brand image toward the community or institution. It means that, indirectly, imaging of a certain community or institution can be built up by the uniform adjusted to its vision and mission. One of the efforts is through â€œPenciptaan Motif Batik Untuk Seragam (Uniform) Civitas Akademika ISI Surakarta Sebagai Upaya Pencitraan Institusi Yang Berkarakterâ€ (Creating A Batik Motive for Uniform of All Staffs in ISI Surakarta as An Effort to the Imaging of A Characteristic Institution). The motives that can be created have some elements that are motives of logo ISI Surakarta, the gate of ISI Surakarta, Pendapa (grand hall), book and lotus flower as well as plants â€œlungâ€. The motive elements are held together to be the symbol of ISI Surakarta as a home for togetherness in reaching the highest ideals in the field of science, art and culture including education, research, and workmanships, as well as community services by upheld the sustainable honesty and integrity. The color of purple represents greatness. Keywords: character, batik motive, imaging